Peningkatan Kinerja Melalui Penguatan Pemberdayaan, Kepemimpinan Transformasional dan Trust:: Penelitian Analisis Jalur dan Analisis SITOREM pada Guru di SMA Negeri 1 Tenjolaya Kabupaten Bogor - Abidin, Zainal (STIT Sirojul Falah Bogor, 2022)
This study aims to determine the efforts to improve teacher performance through a study of the direct influence of the variables of empowerment, transformational leadership and trust. This study uses a survey method with a path analysis approach followed by SITOREM analysis. The results of this study conclude that: (1) There is a direct influence of empowerment on teacher performance with a value of Y1 = 0.342., (2) There is a direct influence of transformational leadership on teacher performance with a value of X3 = 0.126., (3) There is a direct effect of trust on performance teachers with a value of X3 = 0.175., (4) There is a direct influence of empowerment on trust with a value of X31 = 0.159., (5) There is a direct influence of transformational leadership on trust with a value of X32 = 0.212,. The results of the SITOREM analysis show that the indicators that are still weak and need to be improved are; 1) competency building, 2) organizational support, 3) communication between subordinates and superiors, 4) flexibility in working. 4) ideal influence, 5) inspiring motivation, 6) intellectual stimulation, 7) individual attention, 8) partnership strength, 9) ready to accept risk and 10) trust in the expertise possessed. Keywords: empowerment, transformational leadership, trust, teacher performance.